Preventive Strategies against Students’ Moral Degradation through Islamic Religious Education at SMP Negeri 3 Aceh Barat - Sri Hardianty; Fitriani, Nidia; Ismawan, Dana (ISTIFHAM, 2025)
The development of information and communication technology in the digital era has significantly impacted adolescent morality, including that of junior high school students. This study aims to describe the forms of moral degradation occurring among students, analyze the roles and strategies of Islamic Religious Education (IRE) teachers in preventing moral decline, and identify supporting and inhibiting factors in implementing these strategies at SMPN 3 Aceh Barat. This research employs a descriptive qualitative approach with purposive sampling to determine informants: the school principal, five IRE teachers, and five students. Data were collected through interviews, observations, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The validity of the findings was ensured through source and technique triangulation. The findings reveal that although students’ overall moral behaviour is considered reasonably good, various forms of moral degradation are still evident, such as low discipline, lack of courtesy, and misuse of social media. IRE teachers play a strategic role through exemplary behaviour, integrating moral values into instruction, and habituating religious activities at school. Supporting factors for the success of these strategies include teacher commitment, parental support, and a religious school environment. In contrast, the main obstacles include external environmental influences, low internal motivation among students, and limited parental supervision. This study recommends strengthening the synergy between schools, families, and communities to foster morally upright and virtuous student character.